2008
DOI: 10.1007/s00467-007-0706-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of autosomal dominant polycystic kidney disease (ADPKD): the new horizon for children with ADPKD

Abstract: Polycystic kidney disease (PKD) is the most common inherited renal disorder. Patients with PKD remain clinically asymptomatic for decades, while significant anatomic and physiologic systemic changes take place. Sequencing of the responsible genes and identification of their protein products have significantly expanded our understanding of the pathophysiology of PKD. The molecular basis for cystogenesis is being unraveled, leading to new targets for therapy and giving hope to millions of people suffering from P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 68 publications
2
19
0
1
Order By: Relevance
“…Only one child with PKD1 had decreased GFR. This is in agreement with the known fact that, in childhood, renal function is well preserved in the majority of patients and that GFR begins to decline after the paediatric age [29]. The patient with decreased GFR was diagnosed at the age of 2 years because of the positive family history of ADPKD; at the time of the study he was 3 years old.…”
Section: Discussionsupporting
confidence: 84%
“…Only one child with PKD1 had decreased GFR. This is in agreement with the known fact that, in childhood, renal function is well preserved in the majority of patients and that GFR begins to decline after the paediatric age [29]. The patient with decreased GFR was diagnosed at the age of 2 years because of the positive family history of ADPKD; at the time of the study he was 3 years old.…”
Section: Discussionsupporting
confidence: 84%
“…Because nephromegaly in adults with ADPKD positively correlates with the progression of renal excretory failure [36,37], clinical trials with the aim of reducing kidney cyst growth are currently underway in this population [1,[38][39][40][41]. The availability of proven effective treatment would clearly affect the indication for diagnostic screening of at-risk children.…”
Section: Discussionmentioning
confidence: 97%
“…MRI studies [89] have revealed that hepatic cysts are present in 83% of individuals between 15 and 46 years of age and in 55% of patients between the ages of 15 and 25 years [90]. These data suggest that hepatic cysts may be common in children with ADPKD, and like pancreatic cysts, when present, may clearly differentiate ADPKD from ARPKD.…”
Section: Adpkd-clinical Featuresmentioning
confidence: 96%
“…A unilateral presentation of renal cysts with renal enlargement is not uncommon in children. Hypertension can present during the newborn or infant periods and is common in pediatric and young adult ADPKD patients, despite normal renal function [32,59,90,94,98]. Young hypertensive children with ADPKD may present with acute congestive heart failure [21].…”
Section: Adpkd-clinical Featuresmentioning
confidence: 99%